CHANGES IN ANTHROPOMETRIC PARAMETERS IN VITAMIN D DEFICIENCY IN 7-11-YEAR-OLD CHILDREN. (Multidisciplinary Journal of Science and Technology, 2024)
The article discusses issues related to the negative impact of vitamin D deficiency on the body of low birth weight, prematurely born and full-term newborns. A review of the results of studies examining vitamin D availability is presented in pregnant women and their newborn children. There has been a wide prevalence of vitamin D deficiency in women during pregnancy, as well as in newborns. It has been shown that insufficient antenatal supply of vitamin D to the fetus can lead not only to congenital rickets and hypocalcemic neonatal convulsions during the newborn period, but also determines an increase in the incidence of necrotizing enterocolitis and bronchopulmonary dysplasia, as well as disorders of psychophysical development and an increased risk of developing lower respiratory tract infections (bronchiolitis, pneumonia) throughout first year of life.